Implementasi Teknik Outbound untuk Meningkatkan Interaksi Sosial di Kelas X Fase E 5 SMA Negeri 9 Kota Jambi - Sinta Marito Siringo Ringo; Rasimin Rasimin; Hera Wahyuni (Departement of Mathematics Education, 2023)
This research is motivated by the phenomenon of low social interaction among students at school, social interaction is a reciprocal relationship carried out by individuals with individuals, individuals with groups and groups with groups. Therefore the research aims to increase student social interaction by using outbound techniques to increase student social interaction in class X FASE E 5 SMA Negeri 9 Jambi City. This study aims to see a comparison of social interaction before and after being given treatment during the pretest and posttest. This type of research uses a pre-experimental design with the form of a one group pretest-posttest design. The sample in this study amounted to 12 students who were determined using purposive sampling. By using a Likert scale questionnaire as data collection consisting of five answer options. The research results show that outbound can increase students' social interaction. Students' social interaction before being given treatment (pretest) was in the middle group with a percentage of 58%. Whereas after being given the treatment (posttest) social interaction students are in the high group with a percentage of 77%. In the results of the T-test, the value of t-count = 13.9 is obtained, while t-table = 2.228. So that when the hypothesis formula t-count> t-table is entered, Ho is rejected and Ha is accepted. From these results it can be concluded that outbound techniques can improve students' social interaction.